Electronic Trial in Criminal Cases During The Covid-19 Pandemic (Study At The Purwokerto District Court) - Indriyani Novitasari; Indriati Amarini; Astika Nurul Hidayah (Faculty of Law Universitas Muhammadiyah Purwokerto, 2021)
AbstractThe Covid-19 pandemic outbreak in 2020 also affected the implementation of the trial in Indonesia. As an effort to prevent the spread of Covid-19, the trial was conducted electronically, without presenting the litigants. This needs to be done to ensure health, safety, and guarantee legal certainty for justice seekers. This study uses a normative juridical research method. The normative juridical research method is carried out through a literature study that examines secondary data in the form of laws and regulations, court decisions, agreements, contracts, or other legal documents, as well as research results, study results, and other references. The results of this study are gems, electronic hearings in criminal cases during the Covid-19 pandemic at the Purwokerto District Court continue to be carried out by taking into account the standard protocols for preventing and handling Covid-19. Second, there are several obstacles faced by the electronic trial in criminal cases during the Covid-19 pandemic at the Purwokerto District Court. The implementation of electronic hearings in criminal cases during the Covid-19 pandemic is the right solution, innovation, and breakthrough in efforts to prevent the transmission of Covid-19 as regulated in Supreme Court Regulation (Peraturan Mahkamah Agung, PERMA) Number 4 of 2020 concerning Administration and Trial of Criminal Cases in Electronic Court.Keywords: Electronic Court, Covid-19 Pandemic, Legal Certainty